The Unlearned Environment - Berkowitz, Lee R. (British Journal of Healthcare and Medical Research, 2023)
Another day on the wards. I am working with 3 internal medicine residents, a medical student, and a pharmacist. We have 20 patients to see including 4 patients that were admitted overnight. Due to the full capacity of the hospital, our patients are in the ER, an intermediate care unit, and 3 separate hospital wards. Our goal is to finish rounds in 3 hours. Otherwise, orders and consultations will be delayed, and discharges will occur late in the day.